Numerical study on the axial compression behavior of composite columns with steel tube SHCC flanges and honeycombed steel web. (15th May 2023) - Ji, Jing; He, Lingjie; Jiang, Liangqin; Zhang, Yunfeng; Liu, Yingchun; Li, Yunhao; Zhang, Zhanbin
Highlights: Combining with strain hardening cementitious composites (SHCC) material and honeycombed columns, a novel composite column is proposed, and simulation analysis for axial compression behavior of the columns is conducted. The most vertical load is borne by SHCC, and the steel web basically does not undertake the load. The holes on the web leads to stress concentration, and a predicted model of yield zone of steel is proposed. The role of honeycombed web on the composite columns is equivalent to that of lattice plate on the lattice special concrete filled steel tubular columns, and the formula for axial compression bearing capacity of novel columns is derived. Abstract: Strain hardening cementitious composites (SHCC) as a newly emerging material has bright application prospect with good ductility and multiple microcracking behaviors. Combining with SHCC new material and new honeycombed steel structures, novel composite columns with steel tube SHCC flanges and honeycombed steel web (STHSC) is proposed in this research. To study the axial compression behavior of STHSC, the finite element model of STHSC is established by ABAQUS. The effects of different parameters on the bearing capacity, ductility and stiffness of STHSC are explored, and the results show that the constraint effect of steel tube has a significant role in ultimate bearing capacity of STHSC. The ductility of STHSC is mainly above 3.50, and STHSC has great initial stiffness. The observed failure mode is categorized into shear failure with local bulging at the middle section. Steel tube has Ludels slip lines and SHCC presents multiple microcracks that lie at an angle of 45 degrees to the edge. The range of expansion displacement for SHCC is from 0.009 to 0.012 times as the length of STHSC. The reasonable model for the yield zone of steel under four stages is described. Moreover, the honeycombed steel web has an excellent role in connecting both flanges, which is equivalent to the effect of lattice plate on the lattice special concrete filled steel tubular columns. Finally, a calculated formula for axial compression bearing capacity of STHSC has been derived with high precision.